2007
DOI: 10.1590/s0036-46652007000600010
|View full text |Cite
|
Sign up to set email alerts
|

First report of rabies in vampire bats (Desmodus rotundus) in an urban area, Ubatuba, São Paulo state, Brazil

Abstract: SUMMARYThe purpose of this report is to record the first case of a hematophagous bat (Desmodus rotundus) infected with rabies virus in an urban area in Brazil. To the authors' knowledge, this is the first such case in Latin America. After discovering a bat in his garden at 10 o'clock in the morning, a resident of Ubatuba municipality asked the Zoonosis Control Center team to visit his home. The animal was caught alive on the same day and sent to the Pasteur Institute laboratory, where it was identified as a De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 3 publications
0
17
0
7
Order By: Relevance
“…Information about the confi rmed Desmodus rotundus rabies cases describes the bats feeding during the day or being found dead in places with cattle or in caves with a large concentration of individuals, in areas with high numbers of bovine cases 19,22 . Only one case of a Desmodus rotundus bat positive for rabies in an urban area has been described in the literature; this bat was found in Ubatuba, State of São Paulo 24 .…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Information about the confi rmed Desmodus rotundus rabies cases describes the bats feeding during the day or being found dead in places with cattle or in caves with a large concentration of individuals, in areas with high numbers of bovine cases 19,22 . Only one case of a Desmodus rotundus bat positive for rabies in an urban area has been described in the literature; this bat was found in Ubatuba, State of São Paulo 24 .…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Regarding the circumstances of locating positive bats, observation showed that 52.59% of the bats were found in atypical situations, such as on the ground, including one report of D. rotundus in a residential garden in an urban area 29 , inside houses (11.34%) and hanging in buildings (8.24%). Two cases of positive colonies captured while roosting in roofs (1.03%) were reported, but the first specimens of these colonies were captured on the ground, leading to the location of the shelter 3,43 .…”
mentioning
confidence: 99%
“…Los autores alertaron a la comunidad sobre el serio problema de salud pública que este hallazgo representaba (33). Sin embargo, los casos brasileños de rabia humana por D. rotundus se han descrito en pobladores de la jungla amazónica (15,17,22).…”
Section: Figuraunclassified